Use of combined hormonal contraceptives among women with systemic lupus erythematosus with and without medical contraindications to oestrogen. (8th February 2019) - Mendel, Arielle; Bernatsky, Sasha; Pineau, Christian A; St-Pierre, Yvan; Hanly, John G; Urowitz, Murray B; Clarke, Ann E; Romero-Diaz, Juanita; Gordon, Caroline; Bae, Sang-Cheol; Wallace, Daniel J; Merrill, Joan T; et al.
Abstract: Objectives: To assess the prevalence of combined hormonal contraceptives (CHCs) in reproductive-age women with SLE with and without possible contraindications and to determine factors associated with their use in the presence of possible contraindications. Methods: This observational cohort study included premenopausal women ages 18–45 years enrolled in the SLICC Registry ⩽15 months after SLE onset, with annual assessments spanning 2000–2017. World Health Organization Category 3 or 4 contraindications to CHCs (e.g. hypertension, aPL) were assessed at each study visit. High disease activity (SLEDAI score >12 or use of >0.5 mg/kg/day of prednisone) was considered a relative contraindication. Results: A total of 927 SLE women contributed 6315 visits, of which 3811 (60%) occurred in the presence of one or more possible contraindication to CHCs. Women used CHCs during 512 (8%) visits, of which 281 (55%) took place in the setting of one or more possible contraindication. The most frequently observed contraindications were aPL (52%), hypertension (34%) and migraine with aura (22%). Women with one or more contraindication were slightly less likely to be taking CHCs [7% of visits (95% CI 7, 8)] than women with no contraindications [9% (95% CI 8, 10)]. Conclusion: CHC use was low compared with general population estimates (>35%) and more than half of CHC users had at least one possible contraindication. Many yet unmeasured factors, including patient preferences, may have contributed to these observations. Further work should also aim to clarify outcomes associated with this exposure.